Redescription and lectotype designation of Chasmogenus abnormalis (Sharp), with notes on its distribution - Devi, M. Bhubaneshwari; Devi, O. Sandhyarani; Fikáček, Martin; Minoshima, Yûsuke N.; Wanghengbam, Leiphon (Zootaxa, 2016)
Chasmogenus Sharp, 1882 is a relatively small genus of 43 described species of aquatic beetles assigned to the subfamily Acidocerinae of Hydrophilidae (Hansen 1999; Short & Hebauer 2006; Short & Fikáček 2011, 2013; Clarkson & Ferreira-Jr. 2014). It is distributed in all zoogeographic regions except the Nearctic, with the highest species richness known from the Afrotropical (18 spp.) and Neotropical (15 spp.) Regions. Only four species have been described from the Oriental Region: C. abnormalis (Sharp, 1890), C. rubricollis (Régimbart, 1903), C. larsi Hebauer, 1995, and C. cattienus Hebauer, 2002. Of these, only C. abnormalis was recorded multiple times after its description